Plasma Glutamine Is a Minor Precursor for the Synthesis of Citrulline: A Multispecies Study. Issue 4 (8th March 2017) - Marini, Juan C; Agarwal, Umang; Didelija, Inka C; Azamian, Mahshid; Stoll, Barbara; Nagamani, Sandesh CS
Abstract: Background: Glutamine is considered the main precursor for citrulline synthesis in many species, including humans. The transfer of 15 N from 2-[ 15 N]-glutamine to citrulline has been used as evidence for this precursor-product relation. However, work in mice has shown that nitrogen and carbon tracers follow different moieties of glutamine and that glutamine contribution to the synthesis of citrulline is minor. It is unclear whether this small contribution of glutamine is also true in other species. Objective: The objective of the present work was to determine the contribution of glutamine to citrulline production by using nitrogen and carbon skeleton tracers in multiple species. Methods: Humans ( n = 4), pigs ( n = 5), rats ( n = 6), and mice ( n = 5) were infused with L-2-[ 15 N]- and L-[ 2 H5 ]-glutamine and L-5, 5-[ 2 H2 ]-citrulline. The contribution of glutamine to citrulline synthesis was calculated by using different ions and fragments: glutamine M+1 to citrulline M+1, 2-[ 15 N]-glutamine to 2-[ 15 N]-citrulline, and [ 2 H5 ]-glutamine to [ 2 H5 ]-citrulline. Results: Species-specific differences in glutamine and citrulline fluxes were found ( P < 0.001), with rats having the largest fluxes, followed by mice, pigs, and humans (all P < 0.05). The contribution of glutamine to citrulline as estimated by using glutamine M+1 to citrulline M+1 ranged from 88% in humans to 46% in pigs. However, the use of 2-[ 15 N]-glutamine and 2-[ 15 N]-citrulline as precursor and product yielded values of 48% in humans and 28% in pigs. Furthermore, the use of [ 2 H5 ]-glutamine to [ 2 H5 ]-citrulline yielded lower values ( P < 0.001), resulting in a contribution of glutamine to the synthesis of citrulline of ∼10% in humans and 3% in pigs. Conclusions: The recycling of the [ 15 N]-glutamine label overestimates the contribution of glutamine to citrulline synthesis compared with a tracer that follows the carbon skeleton of glutamine. Glutamine is a minor precursor for the synthesis of citrulline in humans, pigs, rats, and mice.